2021
DOI: 10.21203/rs.3.rs-616980/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Clinical Observational Study on the Application of Enhanced Recovery After Laparoscopic Pancreaticoduodenectomy

Abstract: Background: The safety and feasibility of enhanced recovery after surgery (ERAS) for laparoscopic pancreaticoduodenectomy (LPD) are unclear. The aim of this retrospective clinical study was to evaluate the impact of ERAS protocols for LPD.Methods: Between March 2016 and December 2018, a total of 34 consecutive patients with ERAS for LPD were prospectively enrolled and compared with 68 consecutive patients previously treated for non-ERAS after LPD during an equal time frame. The intraoperative and postoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…For surgery, prolonging the operation time will have a negative impact on the prognosis of patients, such as the incidence of surgical site infection, pulmonary infection, sepsis, and septic shock will increase. 7 PD is the most complicated type of abdominal surgery, and the operation time also increases accordingly, which may be one of the factors that affect the overall incidence of postoperative complications of PD far higher than other abdominal surgery. Some studies have shown that prolonging the operation time will increase the perioperative complications and mortality of PD.…”
Section: An Assessment Of Perioperative Outcomes For Open Laparoscopi...mentioning
confidence: 99%
“…For surgery, prolonging the operation time will have a negative impact on the prognosis of patients, such as the incidence of surgical site infection, pulmonary infection, sepsis, and septic shock will increase. 7 PD is the most complicated type of abdominal surgery, and the operation time also increases accordingly, which may be one of the factors that affect the overall incidence of postoperative complications of PD far higher than other abdominal surgery. Some studies have shown that prolonging the operation time will increase the perioperative complications and mortality of PD.…”
Section: An Assessment Of Perioperative Outcomes For Open Laparoscopi...mentioning
confidence: 99%